PENGEMBANGAN MEDIA PEMBELAJARAN KARSUNO(KARTU SUSUN DOMINO) BERBASIS ETNOMATEMATIKA BERBANTUAN APLIKASI CANVA PADA MATERI BANGUN RUANG SISWA SMP KELAS VII - Siti Nurhalizah; Nur Aini S. (Jurnal Manajemen Pendidikan, 2026)
This study aims to develop KARSUNO (Domino Arrangement Cards) an ethnomathematics-based learning medium created using Canva for the topic of 3D shapes in 7th-grade junior high school mathematics; to determine the medium's practicality; and to assess its effectiveness regarding student learning outcomes. This study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 7th-grade students at SMP Hidayatul Kholil. Research instruments included expert validation sheets, student response questionnaires, and pre-test and post-test assessments. Data were analyzed using quantitative descriptive methods to determine the medium's validity, practicality, and effectiveness. The results indicate that the KARSUNO medium meets the criteria for validity, practicality, and effectiveness in improving student learning outcomes. The novelty of this study lies in the development of a Canva-based digital domino game that integrates ethnomathematics specifically local Madurese culture as the context for learning about 3D shapes. Consequently, the KARSUNO medium is suitable for use as an alternative tool for teaching the topic of 3D shapes in mathematics.